Wrecked : deinstitutionalization and partial defenses in state higher education policy - Taylor, Barrett Jay (Rutgers University Press, 2022)
"Higher education is a central institution in U.S. democracy. In the 2010s, however, many states that spent previous decades building up their higher education systems began to tear them down. Growing hostility toward higher education reflected changing social forces that remade the politics of U.S. higher education. The political Right became increasingly reliant on angry white voters as higher education became more racially diverse. The Republican party became more closely connected to extremely wealthy donors as higher education became more costly. In Wrecked, Barrett J. Taylor shows how these social changes set a collision course for the Right and higher education. These attacks fed a policy agenda of deinstitutionalization, which encompassed stark divestment from higher education but was primarily characterized by an attack on the institution's social foundation of public trust. In response to these attacks, higher education officials have offered a series of partial defenses that helped higher education to cope in the short-term but did nothing to defend the institution itself against the long-term threat of declining public trust. The failure to address underlying issues of mistrust allowed conflict to escalate to the point at which many states are now wrecking their public higher education systems. Wrecked offers a unique and compelling perspective linking higher education policymaking to broader social and political forces acting in the twenty-first century"--